EVALUASI PEMBELAJARAN MATA KULIAH AL-ISLAM DAN KEMUHAMMADIYAHAN SEBAGAI INTERNALISASI PENGUATAN PENDIDIKAN KARAKTER MAHASISWA PRODI PAI DI UNIVERSITAS MUHAMMADIYAH TANGERANG - Subarkah, Milana Abdillah; Salim, Agus (Universitas Muhammadiyah Tangerang, 2020)
The phenomenon of education in higher education for students is able to contribute to the aspects of temperament. This is due to various kinds of influences in social life that are currently undergoing many changes. The change in question is an evaluation of learning by integrating character education. Character education can be realized in the regulatory system applied to educational institutions including tertiary institutions. Policy makers have a major contribution as education practitioners, and are also the spearhead of the success of achieving character education for students. This study tries to describe the implementation of learning evaluation of Al-Islam and Kemuhammadiyahan (AIK) courses at the PAI Study Program at the Muhammadiyah University of Tangerang as a reinforcement of character education at Muhammadiyah colleges. The procedure of this research is by observing the activities of lecturers and students when learning takes place then analyzing whether the implementation of evaluation in the faith-based learning is able to foster student character education.